Review of Knowledge Management Integration into Strategic Corporate Decision-Making Processes (International Journal of Scientific Research in Science and Technology, 2025)
In today’s volatile, uncertain, complex, and ambiguous (VUCA) business environment, strategic corporate decision-making is pivotal for organizational resilience and competitive advantage. Knowledge management (KM), the systematic process of capturing, organizing, and utilizing organizational knowledge, has emerged as a transformative tool for enhancing strategic decisions by leveraging intellectual capital. This paper provides a comprehensive review of KM integration into strategic corporate decision-making processes, exploring its theoretical underpinnings, practical applications, and impact on organizational performance across diverse industries. Through a systematic literature review, the study synthesizes insights from management, information systems, organizational behavior, and innovation studies, identifying critical mechanisms such as knowledge sharing, data analytics, collaborative platforms, and adaptive learning systems that enable KM to inform and optimize strategic choices. The review adopts a mixed-method approach, combining qualitative thematic analysis with quantitative evaluation of KM outcomes, such as decision quality, innovation rates, and organizational agility. Key findings reveal that effective KM integration enhances strategic decision-making by fostering a culture of knowledge creation, improving access to actionable insights, and enabling rapid adaptation to market changes. However, challenges like cultural resistance, technological barriers, data silos, and misalignment with corporate objectives hinder successful implementation. A proposed conceptual framework outlines a structured approach to KM integration, emphasizing alignment with strategic goals, stakeholder engagement, and continuous learning to address these challenges. For business leaders, the review offers actionable strategies to design and implement KM systems that support strategic objectives, while policymakers can draw insights into fostering knowledge-driven economies through supportive regulations and infrastructure. The study contributes significantly to management literature by bridging theoretical gaps between KM and strategic decision-making, offering a robust, scalable model for organizations to navigate dynamic markets. By highlighting best practices, addressing implementation barriers, and proposing future research directions such as the role of artificial intelligence in KM and its application in small and medium enterprises (SMEs), this review underscores the transformative potential of KM in shaping strategic corporate decision-making. Ultimately, it positions KM as a cornerstone of organizational success, driving innovation, resilience, and sustainable growth in an increasingly competitive global landscape.